Developing Effective Instructional Design for Fiqh Reading Materials in Islamic Education - Iryanti, Nurlista; Oviyanti, Fitri (Global Expert: Jurnal Bahasa dan Sastra, 2025)
This research aims to develop an effective instructional design for Fiqh reading materials in the context of Islamic education. Fiqh, as an integral part of Islamic religious studies, requires a systematic and structured approach to learning to facilitate deep understanding. An appropriate instructional design can increase learning efficiency, improve information retention, and promote practical application of Fiqh knowledge. This research proposes a systematic approach to developing Fiqh reading materials, covering the identification of learning objectives, audience analysis, relevant teaching strategies, and comprehensive evaluation. The methodology for developing these materials includes planning, development, implementation, and evaluation stages, which collectively support the achievement of effective learning objectives. The proposed instructional design incorporates the application of constructivist learning theory and contextual approach in compiling Fiqh reading materials. Based on this research, the results show that the use of an appropriate instructional design can facilitate better understanding of Fiqh principles and increase active student engagement in the learning process. Keywords: Instructional Design, Reading Materials, Fiqh, Islamic Education